Hygrothermal effect on mechanical properties of composite materials - Ong, Jing Wen (2017)
Fibre reinforced polymer (FRP) composites have been the popular choice in many marine and aeronautical applications over the years. They exhibit good mechanical properties such as high strength and modulus-to-weight ratio and high resistance to fatigue and corrosion which made them a viable material option. However, the susceptibility to long-term moisture exposure and high temperature of the FRP composites and the change in their properties when using them for different applications are the primary concern problems. In this research, it investigates the performance of the hygrothermal aging fatigue behavior of the glass fibre reinforced bismaleimide (BMI) composites in prolonged exposure to elevated temperature saline condition and estimates the durability of the composite material in these environmental conditions. The End Notched Flexure (ENF) test was conducted for the fracture toughness testing and fatigue testing to analyse the Mode II interlaminar fracture toughness and delamination onset and growth behavior. Two sets of glass fibre BMI specimens were prepared under dry and wet conditions. The specimens used for wet conditions were immersed in artificial seawater at diffusion temperature of 50°C. The effects of aging on the flexural stiffness of BMI composites subjected to combined seawater at high temperature and cyclic bending loading were examined. Water diffusion process was found to accelerate at high temperature and result in higher degradation of the material. The glass transition temperature (Tg) of the BMI composite is lowered from the plasticization effect caused after seawater immersion. All specimens exposed to moisture suffered a loss in fracture toughness but experienced a slower fatigue delamination growth rate than the dry specimens, and hence an increase in the number of cycles for crack initiation.